Application of Secant Piles for Excavation Pit in Complicated Environment. Issue 3 (April 2021) - Cui, Meng; Fu, Xiao; Hu, Linna; Liu, Hailin
Abstract: In order to study the application of secant pile in deep foundation pits in complex environments, this paper takes an actual foundation pit project as the research background, and combines the characteristics of the deep excavation of the foundation pit and the large influence of the groundwater level. Propose the design scheme of partition and segment and use finite element analysis method for numerical calculation. By calculation it is known that the overall displacement of the foundation pit support system is 13.11 mm, the maximum horizontal displacement is 11.8 mm, and the ground settlement is 5.7 mm. All indexes meet the requirements of foundation pit specifications. The research results show that the secant pile has its unique advantages and applicability, which can effectively stabilize the overall performance of the foundation pit and the surrounding environment. The design philosophy in this article can provide references for similar foundation pit projects.